Localization of S protein and its relationship to the membrane attack complex of complement in renal tissue. - Falk, R. J. (1987)
The S protein (S) binds to the attack complex of complement (C5b-9) in plasma preventing cytolysis. Using immunofluorescence microscopy, the authors determined the distribution of S in human renal tissue and its relationship to C5b-9, immunoglobulins, C3, albumin, and fibronectin. They examined normal and diseased human kidney tissue from patients with several forms of glomerulonephritis, diabetic nephropathy, and arterionephrosclerosis. S and C5b-9 were found in all diseased tissues; their amounts and distribution directly correlated with severity and location of injury. S and C5b-9 were colocalized in all immune deposits and in all injured glomeruli, tubular basement membranes, and vessel walls. Other than within immune deposits, S and C5b-9 were usually not colocalized with C3. This study demonstrates that S is deposited in areas of tissue injury and thus may participate in the pathogenesis of renal damage. Because in tissue S and C5b-9 are always associated, the attack complex in tissue must either be derived from the circulation as SC5b-9 or it must be capable of binding S after the formation in situ of C5b-9.